Domination numbers of cardinal products of graphs : dissertation - Klobučar, Antoaneta; Seifter, Norbert; Svrtan, Dragutin; Veljan, Darko ([Zagreb] : A. Klobučar, 1997)
Summary: In this work the explicit formulas for the domination numbers of the cardinal products of two paths and twocycles are given. Beside this it has been examined when Vizing's conjecture holds, in other words when for two graphs G and H [gama](G*H=[gama](G).[gama](H) holds. The limits lim and lim are given, too. At the end of the work the k-domination is treated, as a generalized term of domination, as well as explicit formulas for k-domination numbers of cardinal products two paths and two cycles.
Sažetak: U ovm radu daju se eksplicitne formule za dominacijske brojeve na kardinalnom produktu dva puta i dva ciklusa. Osim toga proučavaju se slučajevi kada vrijedi Vizingova pretpostavka, odnosno kada za dva grafa G i H vrijedi [gama](G*H)=[gama](G).[gama](H). Izračunani su islijedeći limesi: lim i lim . Na kraju rada razmatra se slučaj k-dominacije, kao popćenja pojma dominacije i daju se eksplicitne formule za k-dominacijske brojeve na kardinalnom produktu dva puta, odnosno dva ciklusa.
Doktor prirodnih znanosti - matematika
Mentori: N. Seifert, D. Svrtan, D. Veljan; datum obrane: 09.07.1997.
University of Zagreb, Department of Mathematics, [Zagreb], [1997.]
Bibliografija: str. 74-79
Summary
Keywords: Teorija grafova -- Vizingova pretpostavka; Teorija grafova -- Strukturne osobine grafova